PENGARUH LITERASI KEUANGAN SYARIAH, KEPERCAYAAN, DAN PELAYANAN SYARIAH TERHADAP PREFERENSI TABUNGAN BSI - Putri, Putri Heriska (Islamic Economics and finance in Focus, 2022)
Sharia savings products are one of the instruments used by the public to be a place to store assets. BSI is one of the largest Islamic banks in Indonesia that provides many sharia savings product services. The purpose of this study was to determinate how the influence of sharia literacy, customer trust, and sharia banking services on the preference for using BSI sharia savings products. This study uses quantitative methods with multiple linear regression analysis. This study uses primary data in the form of questionnaires and secondary data obtained from the result of literature studies an journals. This research was conducted at BSI KC Malang Sutoyo with a total of 100 respondents. In this study, the tools used to manage data were using IBM SPSS Ver. 23. The result of this study found that Islamic financial literacy, cutomer trust, and Islamic banking services both partially and simultaneously affect the preference for using sharia savings products at BSI KC Mlang Sutoyo.